Empowering healthy communities - Forsgren, Nicole; Ceccarelli, Greg; Jedamski, Derek; Kelly, Scot; Sullivan, Clair (The State of the Octoverse, 2020)
As the largest developer platform with more than 56 million developers worldwide, GitHub is in a unique position to provide analysis and speak to trends about communities and collaboration in open source. Understanding how people interact gives us all insights to help create successful models for the future. Our analysis spans several years, depending on the community we are investigating, so we can see how communities grow and change over time. Featuring contributions from Greg Ceccarelli, Denae Ford, Vannessa Gennarelli, Yu Huang, Tom Zimmerman